Leadership, Trustworthiness, and Ethical Stewardship. - Caldwell, Cam (ĐHKT, 2016)
In this article, we present empirical results indicating that when leadership behaviors are perceived as trustworthy through the observer's mediating lens, trust increases and leaders are more likely to be viewed as ethical stewards who honor a higher level of duties. This article contributes to the growing body of hterature about the importance of ethical stewardship in the trust relationship.